PENGATURAN TANGGUNG JAWAB KURATOR TERHADAP PENGURUSAN DAN PEMBERESAN HARTA PAILIT DALAM KAITANNYA DENGAN HAK KREDITOR SEPARATIS - Dewi Tuti Muryati; Dhian Septiandani; Efy Yulistyowati (Jurnal Dinamika Sosial Budaya, 2017)
Bankrupt is a situation where the debtor is unable to make payments on his debts to one or more creditors. With the general confiscation against the bankruptcy estate, the management and settlement of property made by a debtor or a curator or Heritage Hall (BHP) under the supervision of the Supervisory Judge who appointed simultaneously by the Commercial Court at the time of the decision of a declaration of bankruptcy debtors. This is in accordance with the provisions of Article 69 paragraph (1) of Law No. 37 of 2004 which states that "the task of the curator is to perform maintenance and bankruptcy assets or settlement". The problems studied were the setting responsibilities in the management and settlement curator of the bankruptcy estate pursuant to Act No. 37 of 2004 on Bankruptcy and PKPU, and the responsibility of the curator and the obstacles encountered on the fulfillment of the rights of creditors in the administration and settlement of separatist bankruptcy assets. The method used in this research is normative juridical approach; specification research is descriptive; methods of sampling conducted with a purposive, methods of data collection using secondary data and primary data. Secondary data used include the primary legal materials, secondary law, and tertiary legal materials; then analyzed qualitatively. The survey results revealed that the setting responsibilities curator of the management and settlement of the treasure stipulated in Article 69 paragraph (1), Article 15 paragraph (3), Article 16 paragraph (1), Article 98, Article 99 of Law No. 37 of 2004, which in essence, is to carry out all efforts to secure the bankruptcy estate for the benefit of the debtor and the creditors. If the responsibility of the curator in the management and settlement bankruptcy estate associated with the rights of creditors separatists, based on Law No. 37 of 2004 on Bankruptcy and PKPU requires that efforts are made to increase the economic value of the bankruptcy estate, with the hope of the rights of all creditors especially creditors take precedence right, can be met in accordance with the amount of receivables. Curators are also required to have high integrity, professional and adhere to professional and ethical standards.